Essential mathematics and statistics for forensic science - Adam, Craig (Wiley, 2010)
This text is an accessible, student-friendly introduction to the wide range of mathematical and statistical tools needed by the forensic scientist in the analysis, interpretation and presentation of experimental measurements.